Analisis Perbandingan Menggunakan Model Altman Z-Score dan Zmijewski dalam Memprediksi Potensi Kebangkrutan Perusahaan - Mustika, Mustika; Rahmi, Elvi; Putra, Defriko Gusma (Universitas Negeri Padang, 2025)
This study aims to determine whether there are differences in bankruptcy prediction results between the Altman Z-Score and Zmijewski models, and find out the most accurate model in predicting bankruptcy in clothing and luxury goods subsector companies included in the consumer cyclical sector and listed on the Indonesia Stock Exchange (IDX) during the 2019-2023 period. This research is a type of comparative quantitative research. The population in the study included all clothing and luxury goods subsector companies listed on the IDX in that year, with purposive sampling technique used to determine the sample so that 19 companies were obtained as research objects. The data analysis technique used is a nonparametric statistical test, namely the Wilcoxon Signed Rank Test, with the help of SPSS version 26 software, as well as an accuracy level test to compare the accuracy of the Altman Z-Score and Zmijewski models. The results showed that there was a significant difference between the prediction results of the two models, and the Zmijewski model was proven to have the highest level of accuracy, which amounted to 89,47%, with a type I error rate of 10,53% and a type II error of 0%.